Role of fine-needle aspiration cytology in the evaluation of salivary gland lesion with utilization of Milan system for reporting - Alka Ambedkar; Rashmi Nayak; Mangeet Dhurve; Kavita Sachdewa; Jagmohan Singh Dhakar (Asian Journal of Medical Sciences, 2024)
Background: Fine-needle aspiration cytology (FNAC) plays a role in the pre-operative diagnosis of salivary gland mass lesion. Salivary gland neoplasm accounts for 6% of all head and neck tumors. It is widely used safe and relatively non-traumatic procedure that can quickly provide important information. “The Milan system for reporting salivary gland cytopathology” (MSRSGC) was introduced, providing a guide for diagnosis and management according to the risk of malignancy (ROM) in different categories.